SFDRS as a metalanguage for ‘foodscaping’: adding a formal dimension to an interdisciplinary, multimodal approach to food - Kim, Loli; Calway, Niamh (Frontiers in Communication, 2024)
‘Foodscaping’ seeks to understand how meaning is made through humans’ interaction with food in particular environments through a multimodal and interdisciplinary analytical lens. As part of a foodscaping project, researchers often interpret food environments to which they are not intimately ‘local’. This presents cross-cultural limitations in the production of analysis. Most pertinently, how can personal interpretation be divorced from locally salient and meaningful discourses? This paper presents the findings of a pilot foodscaping analysis using the box notation style of Kim’s Korean Segmented Film Discourse Representation Structures (K-SFDRS). K-SFDRS notation, developed to provide both coarser- and finer-grained formal transcription for South Korean multimodal film discourse analysis, is tested as an analytic tool for an authentic South Korean foodscaping experience. This paper aims to ascertain whether the formal nature of K-SFDRS transcription is a useful aid to the analysis of a foodscape, which otherwise risks relying heavily on personal interpretation. This pilot study presents an introduction to both foodscaping and (K-)SFDRS, outlines the potentials of (K-)SFDRS notation within a foodscaping context, offers a step-by-step outline for constructing K-SFDRS box notation using an exemplar South Korean foodscape, and finally demonstrates how this box notation may be used in the support of foodscaping analysis in various interdisciplinary channels. During this pilot study, the authors make a novel methodological development in the form of what they term ‘cluster structures’, which overcome the problems presented by the lack of cinematic narrative editing in spontaneous discourse, segmenting meaning into logical forms within which structures of meaning are hierarchised without requiring the discourse relations to structure the logical forms themselves in narrative discourse following the original K-SFDRS methodology. The paper concludes that K-SFDRS, alongside the aforementioned methodological development, has potential to help foodscaping researchers constrain interpretation to salient discourses and direct foodscaping analysis down meaningful avenues. Through its culinary scope, this chapter adds a new disciplinary dimension to discussions of metalanguage and makes an innovative contribution to the current corpus of multimodal research.